Designing Internet Shopping Mall in the Customer Behavior Perspective - Hermawan, Iwan; Sartono; Hindrawati, Gita; Amid, Jusmi; Suwondo, Agus (Conference Series, 2021)
Internet shopping mall (E-mall) is a form of e-shop expansion that has a trading complexity and many product variants. E-mall is still limited in its application because its development requires relatively large capital than building an e-shop. Moreover, the development of application portfolios and architectural design that facilitates how the physical and virtual value chains are elaborated has not been carried out in many system development studies. In designing the portfolio, it is related to the consumer behaviour perspective. The direction of the study is to build an e-mall design concept that elaborates the physical and virtual value chain. The sample of this research is the target consumers who have shopped online as many as 168 respondents in Indonesia. A multivariate statistical study approach using conjoint analysis was employed to develop the E-mall design. This study produces five main dimensions that can be used as a reference for E-mall developers and further develop an application portfolio.